Experimental measure of metal–alkynyl electronic structure interactions by photoelectron spectroscopy: (η5-C5H5)Ru(CO)2CCMe and [(η5-C5H5)Ru(CO)2]2(μ-CC). (28th January 2015) - Head, Ashley R.; Renshaw, Sharon K.; Uplinger, Andrew B.; Lomprey, Jeffrey R.; Selegue, John P.; Lichtenberger, Dennis L.
Graphical abstract: UV photoelectron spectroscopy was used to probe the electronic structure of the alkynyl ligand of (η 5 -C5 H5 )Ru(CO)2 CCMe and [(η 5 -C5 H5 )Ru(CO)2 ]2 (μ-CC). The filled/filled interaction between the ligand π and metal d orbitals, the backbonding capacity of the alkynyl ligand, and the electronic communication between the metal centers is quantified from the ionization energies. Abstract: The gas-phase He I and He II photoelectron spectra of the propynylruthenium molecule CpRu(CO)2 CCMe (Cp = η 5 -C5 H5 ) and the ethynediyldiruthenium molecule [CpRu(CO)2 ]2 (μ-CC) are compared with the spectrum of CpRu(CO)2 Cl to experimentally determine electronic structure interactions of the alkynyl ligands with the metal. The spectra indicate that the interaction between the filled metal- d π and filled alkynyl-π orbitals dominates the metal-alkynyl π electronic structure, mirroring previously characterized CpFe(CO)2 alkynyls. All valence ionizations of the Ru molecules are stabilized with respect to similar Fe compounds, contrary to the common expectation of lower ionization energies with atomic substitution down a column of the periodic table. Ab initio electronic structure calculations suggest that this stabilization traces to the greater inherent electronic relaxation energy associated with removal of Fe 3 d electrons compared to removal of Ru 4 d electrons. Destabilization of the first two ionization bands of the diruthenium molecule are a result of filled–filled interactions between alkynyl π-bonds with the symmetric combination of metal–metal- d π orbitals, showing electronic communication between the metals through the alkynyl bridge. From the photoelectron spectrum, this communication was calculated to have a minimum electron-transfer integral of 0.56 eV. The stabilization of the antisymmetric combination of the metal–metal- d π orbitals gives a direct and unique experimental measure of the interaction with the alkynyl π ∗ orbitals. The stabilization caused by the alkynyl π ∗ orbitals was found to be approximately one-third of the destabilization caused by the filled–filled interaction with the alkynyl π-bonds and about one-fourth to one-third the stabilization provided by back-bonding to a carbonyl ligand.